Emission Gas Reducer on Motor Vehicle, Automobile, Light Engine of Boat and Stationary Combustion Engine. - Kusuma, I Gusti Bagus Wijaya (Makara Journal of Technology, 2002)
Emission gas reducer on motor vehicle, automobile, light engine of boat and stationary combustion engine. The use of motor vehicle should be followed by protection against damages on the environment, since the exhaust gas from combustion engine has significantly affect on air and environmental pollution. One method to solve the problems in air pollution has been done by using a re-heater designed in Mechanical Engineering Department, University of Udayana. In accordance to the test on the re-heater, it can be seen very clear that the re-heater has significantly reduce the CO emission of about 54%. It also reduces the CO2 dan HC emission, and in the other side increases the number of O2. The re-heater has no significant effect to engine performance during the operation and also reduces the noise of motor.